Galectin-3 Is a Potential Mediator for Atherosclerosis - Ziyu Gao; Zhongni Liu; Rui Wang; Yinghong Zheng; Hong Li; Liming Yang (Journal of Immunology Research)
Atherosclerosis is a multifactorial chronic inflammatory arterial disease forming the pathological basis of many cardiovascular diseases such as coronary heart disease, heart failure, and stroke. Numerous studies have implicated inflammation as a key player in the initiation and progression of atherosclerosis. Galectin-3 (Gal-3) is a 30 kDa β-galactose, highly conserved and widely distributed intracellularly and extracellularly. Gal-3 has been demonstrated in recent years to be a novel inflammatory factor participating in the process of intravascular inflammation, lipid endocytosis, macrophage activation, cellular proliferation, monocyte chemotaxis, and cell adhesion. This review focuses on the role of Gal-3 in atherosclerosis and the mechanism involved and several classical Gal-3 agonists and antagonists in the current studies.